Tehnologija numerično krmiljenih stružnic z gnanimi orodji: Univerzitetni učbenik - Ficko, Mirko; Berus, Lucijano; Potočnik, David (2021)
Technology of Numerically Controlled Lathes with Driven Tools: University Textbook. The development of machine tools with computer-aided control has increased the capabilities of machining systems and the complexity of technology preparation and programming. Modern numerically controlled lathes with controlled main spindle and driven tools have made it possible to perform complex technological turning and milling operations on the same machine, but require additional knowledge and experience of technologists for efficient use. The book comprehensively covers the field of technology preparation and programming of numerically controlled lathes with driven tools according to the standard ISO and focuses on matters that do not depend on the manufacturers of the machines and controls. Explanations and examples are supported by illustrations, so that the book can be used not only for training but also as a manual in industry. In addition to the basics of programming numerically controlled machines, the most common commands and assumptions used on lathes with driven tools, the book also includes an explanation of thread turning, descriptions of machining cycles that simplify manual programming, and parametric programming to automate the programming of product groups.
Keywords: manufacturing technologies; machine tools; numerical controlled machines; lathes with driven tools; technology preparation; programming opf numerical controlled machine tools